Potential, Characteristics and Utilization of Shrimp Pond Solid Waste as Organic Fertilizer - Suwoyo, Hidayat Suryanto; Tuwo, Ambo; Haryati, Haryati; Anshary, Hilal (International Journal of Environment, Agriculture and Biotechnology, 2019)
The study aimed at determining the potential, characterization and utilization of super-intensive shrimp pond solid waste as a raw material for organic fertilizer, and its application in fisheries and agriculture. It was conducted at Experimental Pond Installation, Research Institute for Coastal Aquaculture and Fisheries Extension located in Punaga Village in South Sulawesi. The research involved 3 of 1,000 m2 concrete ponds for 105 rearing period days and entailed the stocking density of 750-1,250 shrimp/m2. The observation was carried out in the sediments on a wastewater treatment plant (WWTP) with 7,000 m2. The variables observed in this study included sedimentation rate, total sediment, and estimation of total nutrient in the contents of solid waste such as C-organic N total. P2O5. K2O. pH, water content and C/N ratio. The results showed total sediment in the following stocking 750, 1000 and 1,250 vaname shrimp/m2 weighed 18.2, 20.3 and 21.9 tons respectively. During the shrimp cultivation, TN, TP and C accumulated in sediments increased, resulting to an upsurge in stocking density. Therefore, the solid waste may potentially be used as organic fertilizer because it has a fairly high nutrient content such as N total of 0.58%. P2O5 by 3.33%. K2O by 0.8%. C-organic by 9.94%. pH 6.73, water content of 16.36% and C / N ratio by 17.14%.